Peran Guru dalam Membentuk Karakter Siswa Pada Mata Pelajaran Aqidah Akhlak Kelas V di MI NW Penakak - Ittihad (Al-Faiza : Journal of Islamic Education Studies, 2024)
This study was conducted to know the role of teachers in shaping the character of students in the subject of aqidah ahklak class V at MI NW Penakak and to know the morals of class V students at MI NW Penakak. This study is a qualitative study conducted. This type of research is descriptive qualitative research, with Data collection techniques, observation, interview, and documentation methods. Based on the description above, it can be concluded that: first, the role of teachers in shaping the character of students in the subject of Aqidah ahklak in class 5 MI NW Penakak has been carried out very well by the class teacher. There are several roles played by teachers, including: 1). teacher as a facilitator. 2). teacher as a director. 3). teacher as a motivator. second, how are the morals of class V students at MI NW Penakak? Third, there are several supporting and inhibiting factors in the role of aqidah ahklak teachers in shaping the character of class V students of MI NW Penakak, including: 1). supporting factors, including a good school environment, good learning media, good learning facilities, and teachers who can make the class lively and full of enthusiasm: 2). inhibiting factors, including students sometimes not going to school, lack of pocket money, poor student health, there are students from broken homes, and the level of intelligence of each student.